2020
DOI: 10.3390/ijerph17197040
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Relationship between Type 2 Diabetes Mellitus and Employment: Evidence from the Korea Health Panel Study

Abstract: Previous studies have analyzed the impact of diabetes mellitus on labor market participation by men and women, but gender difference between type 2 diabetes mellitus (T2DM) and employment has not been the focus. This study aims to explore gender differences between T2DM and employment status. Data from the Korea Health Panel Study, 2013–2015 were analyzed by distinguishingT2DM and non-diabetes (N = 11,216). The empirical model was established and the generalized two-stage least squares (2SLS) was estimated, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
(29 reference statements)
0
0
0
Order By: Relevance
“…Several studies showed that diabe-tes significantly decreases employment probabilities in general populations. [8][9][10] Our results highlight the detrimental employment impact of diabetes in individual with end-stage renal disease. A study by Nazarov et al showed that the best strategies for returning to work for those with chronic disease are multidisciplinary interventions involving various health and work professionals.…”
Section: Discussionmentioning
confidence: 67%
“…Several studies showed that diabe-tes significantly decreases employment probabilities in general populations. [8][9][10] Our results highlight the detrimental employment impact of diabetes in individual with end-stage renal disease. A study by Nazarov et al showed that the best strategies for returning to work for those with chronic disease are multidisciplinary interventions involving various health and work professionals.…”
Section: Discussionmentioning
confidence: 67%